2022
DOI: 10.1021/acsaem.2c00076
|View full text |Cite
|
Sign up to set email alerts
|

Modification Strategy for Constructing Li Gradient Combined with Spinel Phase Coating on Li-Rich Mn-Based Materials

Abstract: Li-rich layered oxides (LLOs) are considered as the cathode materials for the next generation of lithium-ion batteries because of their high specific capacity. However, due to the structural rearrangement in the charging and discharging process, the initial Coulombic efficiency (ICE) is low and accompanied by serious voltage attenuation and bad cycle performance. In this work, the Li-gradient layer on the surface of the rod-like LLOs is constructed by the treatment of (NH 4 ) 2 SiF 6 under high temperature and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…The 0.2O6–0.8O3 cathode material also exhibits a favorable voltage maintenance ability at 1 C after 100 cycles (Figure b). The voltage drop of the 0.2O6–0.8O3 composite is 0.349 V, which is lower than that of the O3 type (0.455 V) and comparable to that of the O2-Li 1.25– y Mn 0.5 Co 0.25 O 2 material (about 0.23 V of voltage attenuation at 50 cycles) and (NH 4 ) 2 SiF 6 surface treated O3 type material (0.41 to 0.35 V). The O2/O3 symbiotic material prepared by the Dollé team has obvious voltage attenuation, but its voltage drop is between O3 and pure O2 materials, which is consistent with the experimental phenomenon in this work.…”
Section: Resultsmentioning
confidence: 67%
“…The 0.2O6–0.8O3 cathode material also exhibits a favorable voltage maintenance ability at 1 C after 100 cycles (Figure b). The voltage drop of the 0.2O6–0.8O3 composite is 0.349 V, which is lower than that of the O3 type (0.455 V) and comparable to that of the O2-Li 1.25– y Mn 0.5 Co 0.25 O 2 material (about 0.23 V of voltage attenuation at 50 cycles) and (NH 4 ) 2 SiF 6 surface treated O3 type material (0.41 to 0.35 V). The O2/O3 symbiotic material prepared by the Dollé team has obvious voltage attenuation, but its voltage drop is between O3 and pure O2 materials, which is consistent with the experimental phenomenon in this work.…”
Section: Resultsmentioning
confidence: 67%
“…It was shown that the phase structure of the coating consisted of FCC + TiN and a small amount of Laves phase, and the hardness of the coating with Ti elements was significantly increased. 6 Kuang et al to investigate the influence of Nb on the coating organization and properties, Al 2 O 3 /MC particle-reinforced MoFeCrTiW (Al 2 O 3 ) 0.5 Nb HEA coating was on M2 high-speed steel using laser melting technique. It was shown that the increase in Nb content upgraded the stiffness and abrasiveness of the overlay.…”
Section: Related Workmentioning
confidence: 99%
“…CoCr 2 FeNiTi high‐entropy alloy (HEA) coating was on the surface of stainless steel using laser melting technique. It was shown that the phase structure of the coating consisted of FCC + TiN and a small amount of Laves phase, and the hardness of the coating with Ti elements was significantly increased 6 . Kuang et al to investigate the influence of Nb on the coating organization and properties, Al 2 O 3 /MC particle‐reinforced MoFeCrTiW (Al 2 O 3 ) 0.5 Nb HEA coating was on M2 high‐speed steel using laser melting technique.…”
Section: Related Workmentioning
confidence: 99%
“…To date, multifarious approaches have been investigated to stabilize the O-redox process, such as surface coating, [20][21][22] bulk doping [23][24][25][26][27] and surface chemical treatment, 28,29 so as to improve the structural stability of Li-rich cathodes. For instance, Peng et al 30 regulated the O-redox process by the NiFe 2 O 4 coating, which effectively reduces the oxygen accumulation during the cycle to improve the initial coulombic efficiency and reduce the loss of capacity.…”
Section: Introductionmentioning
confidence: 99%